Pengaruh Motto Sekolah “Ramah Anak” terhadap Peningkatan Karakter Siswa - Sinaga, Zito Yonatan; Setiawan, Deny (AS-SABIQUN, 2025)
This research is motivated by the many schools that implement the motto "Child Friendly" which is also inseparable from its goal of making students have good character. The purpose of this study is to find out how the motto of a child-friendly school in forming good character for these students. This study was conducted at SMP Negeri 24 Medan. The theory used is Law Number 35 of 2014 concerning Child Protection by keeping children away from violence and creating students who are responsible for each of their developments. The method used in this study is quantitative. The population in this study were all students of class IX of SMP Negeri 24 Medan totaling 328 students and the number of samples taken in this study was 10% of the number of students in class IX (328) which was 32 students. Sampling was done using random sampling technique. Data collection instruments in this study were questionnaires, observation and documentation. In this study, data analysis used quantitative statistical methods with product moment calculations. Based on the results of the study, it was found that the influence of the school motto "child-friendly" had a low effect of 15.13% on improving the character of class IX students of SMP Negeri 24 Medan. This is evidenced by the calculation of the correlation coefficient between variable x and variable y, it is known that the r-count value is 0.389. If this value is compared with the rtable value at a significance of 5% with n = 32, then the rcount is as large as the provisions, if the rcount value is greater than the rtable value (rcount>rtable) or 0.389>0.349 then the conclusion that can be drawn is that there is a low significant influence between the school motto "child friendly" on improving the character of class IX students at SMP Negeri 24 Medan.